Improving the stability of oil-in-water emulsions by using mussel myofibrillar proteins and lecithin as emulsifiers and high-pressure homogenization. (October 2019) - Cha, Yue; Shi, Xiaojie; Wu, Fan; Zou, Henan; Chang, Chuting; Guo, Yingnan; Yuan, Meng; Yu, Cuiping
Abstract: Emulsifiers are usually incorporated in emulsion preparation to make kinetically stable emulsions. HPH is often used to prepare food emulsions, producing stable emulsion with fine texture. The purpose of this study is to investigate the effect of high-pressure homogenization (HPH) at 40, 80 and 120 MPa on oil-in-water (O/W) emulsion stabilized with mussel myofibrillar proteins (MMP) and lecithin. Emulsifying properties, creaming index, microstructure, particle size and zeta-potential, apparent viscosity of HPH treated emulsions, together with protein solubility and surface hydrophobicity were analyzed. HPH treatment resulted in increase in emulsifying activity index (from 56.93 to 87.68 m 2 /g), emulsifying stability index (from 59.33 to 154.62 min), apparent viscosity and absolute zeta-potential (from 10.67 to 37.03 mV) of MMP and lecithin stabilized O/W emulsion. Droplets size (from 3.95 to 0.46 μm) and creaming index of high-pressure homogenized emulsion reduced. These changes may resulte from the improved solubility (from 16.5% to 75.1%) and exposed hydrophobic groups (from 196.37 to 258.50) of MMP. The most suitable processing pressure to produce fine and stable emulsions was 80 MPa. These results will contribute for improving the formulation of emulsions and their properties and provide new understanding into MMP as a natural emulsifier in the food production. Highlights: There are developed formulations of food emulsions using MMP and lecithin. The best stability of developed emulsions was obtained by applying HPH at 80 MPa. High-pressure homogenization led to the exposure of hydrophobic groups in MMP.